2008
DOI: 10.1080/02643290802299350
|View full text |Cite
|
Sign up to set email alerts
|

Training of familiar face recognition and visual scan paths for faces in a child with congenital prosopagnosia

Abstract: In the current report we describe a successful training study aimed at improving recognition of a set of familiar face photographs in K., a 4-year-old girl with congenital prosopagnosia (CP). A detailed assessment of K.'s face-processing skills showed a deficit in structural encoding, most pronounced in the processing of facial features within the face. In addition, eye movement recordings revealed that K.'s scan paths for faces were characterized by a large percentage of fixations directed to areas outside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…(age 7, Brundson, Coltheart, Nickels, & Joy, 2006;previously reported in Joy & Brundson, 2002) exhibited echolalia (rote repetition of phrases out of context)-again a common feature of speech development in ASD (Tager-Flusberg & Calkins, 1990). Concerns regarding ASD were also raised in the case of K. (age 4, Schmalzl et al, 2008b), although she did not score in the autistic range on the Childhood Autism Rating Scale (Schopler, Reichler, DeVellis, & Daly, 1980). The exception here appears to be L.G.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…(age 7, Brundson, Coltheart, Nickels, & Joy, 2006;previously reported in Joy & Brundson, 2002) exhibited echolalia (rote repetition of phrases out of context)-again a common feature of speech development in ASD (Tager-Flusberg & Calkins, 1990). Concerns regarding ASD were also raised in the case of K. (age 4, Schmalzl et al, 2008b), although she did not score in the autistic range on the Childhood Autism Rating Scale (Schopler, Reichler, DeVellis, & Daly, 1980). The exception here appears to be L.G.…”
mentioning
confidence: 85%
“…For example, she failed to recognize her father when he was wearing the same football strip as his team-mates. A comprehensive study of K 's face recognition difficulties was conducted by Schmalzl et al (2008b), when she was 4 years old. K also has difficulties with social interaction and was suspected of having Asperger syndrome, although diagnostic screening using the Childhood Autism Rating Scale at age 3 concluded that she did not meet criteria for ASD.…”
Section: Cases Child Amentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there has been recent interest in whether face training can improve face recognition ability in prosopagnosia Schmalzl, Palermo, Green, Brunsdon, & Coltheart, 2008) and autism spectrum disorder (Tanaka et al, 2010). Training studies can benefit from the availability of two closely matched tests of face recognition ability, one to assess ability pre training and one to assess ability post training.…”
Section: Individual-differences Studiesmentioning
confidence: 99%
“…However, so far there were only a few attempts to examine whether enhancing holistic processing in prosopagnosic individuals would improve their face processing. For example, K, a 4-years-old child with CP was trained to direct her attention to internal face features thus enhancing their holistic processing (e.g., eyes and nose) and this resulted in improved recognition abilities immediately following training and a month later (Schmalzl, Palermo, Green, Brunsdon, & Coltheart, 2008b). Moreover, following training on discrimination of unfamiliar faces based on spatial configuration, MZ, a 48-years old women with CP, improved her performance on face identification and this was accompanied by a modification of her ERP and fMRI face related signals in terms of selectivity and increased functional connectivity (DeGutis, .…”
Section: Amelioration and Rehabilitation Attempts In Prosopagnosiamentioning
confidence: 99%